A perturbative approach to the non-relativistic string spectrum - Marius de Leeuw; Andrea Fontanella; Juan Miguel Nieto García (Journal of High Energy Physics)
Abstract In this letter we use a perturbative approach to find the spectrum of non-relativistic strings in the String Newton-Cartan (SNC) AdS5×S5 spacetime. We perturb the bosonic sector of the action around a BMN-like folded string solution in light-cone gauge. We find strong evidence that the theory is described by a combination of massive and massless free fields in an anti-de Sitter background by showing that interaction terms up to six scalars vanish after field redefinitions.